Common Errors, Illusions and Myths in Statistical Procedures - KC, Vikash Kumar (Janapriya Journal of Interdisciplinary Studies, 2017)
Statistical Procedure is one of the prime components of research which facilitates to draw firm inference from sample information. Although it has various advantages and strengths, its application sometimes may be misleading because of its assumptions, illusions and complexities. There are many sources of errors that arise from the application of statistical procedures. For example; errors may arise from planning, preparation of research instruments, basic assumptions, application of different research approaches, common errors also occur while reporting the research outcomes and drawing conclusions. Therefore, a grater care is to be paid while applying statistical procedures. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 133-144